Emotion regulation and perceptions of academic stress as key predictors of academic motivation in second language learning. - Haiying Liang; Xu Mao (PLoS ONE)
Motivation, as a driving force of human behavior, is influenced by various psychological factors. Among these, emotion regulation and perceptions of academic stress have received limited attention in the context of second language learning. This study examines the interplay between emotion regulation, perceptions of academic stress, and academic motivation among university students in China who are learning English as a second language. A convenience sample of 1189 university students in China participated in the study. Data were collected using validated emotion regulation, perceptions of academic stress, and academic motivation questionnaires and analyzed using Pearson correlation and multiple regression methods. The results reveal that emotion regulation is strongly and positively correlated with academic motivations (r = 0.73, p < 0.01), while perceptions of academic stress have a strong negative correlation with academic motivations (r = -0.75, p < 0.01). Multiple regression analysis shows that emotion regulation significantly predicts academic motivations (B = 0.442, p < 0.01), explaining 44.2% of the variance, with cognitive reappraisal having the strongest positive effect (B = 0.435, p < 0.01). Conversely, perceptions of academic stress negatively predict academic motivations (B = -0.503, p < 0.01), with academic workload and exams exerting the most substantial negative impact (B = -0.492, p < 0.01). These findings highlight the critical role of emotional regulation in enhancing academic motivation and the detrimental effects of academic stress, particularly related to self-perception, on students' motivation.